Implementasi Kebijakan Program Keluarga Harapan (PKH) Dalam Meningkatkan Kesejahteraan Masyarakat - Mala Sari, Yesi; Pratiwi, Sulis; Mardeansyah, Rizky; Khairunnisa, Naya; Erinaldi, Erinaldi (Civiliza Publishing, 2025)
The Family Hope Program (PKH) is a government policy that aims to reduce poverty through conditional social assistance. This study aims to analyze the implementation of PKH in improving community welfare based on a literature review. The method used is a literature study with a narrative review approach to various journals, scientific articles, and official documents. The results of the study show that PKH contributes to increasing purchasing power, access to education and health, and reducing poverty rates. However, its implementation still faces obstacles such as targeting accuracy, dependence on assistance, limited assistance, and weak coordination between institutions. In conclusion, the effectiveness of PKH is highly determined by the quality of its implementation and the need to integrate it with empowerment programs in order to encourage the independence of Beneficiary Families (KPM).